2015
DOI: 10.4049/jimmunol.1402307
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Psoriatic Skin Inflammation Leads to Increased Monocyte Adhesion and Aggregation

Abstract: Psoriasis patients exhibit an increased risk of death by cardiovascular disease (CVD) and have elevated levels of circulating intermediate (CD14++CD16+) monocytes. This elevation could represent evidence of monocyte dysfunction in psoriasis patients at risk of CVD, as increases in circulating CD14++CD16+ monocytes are predictive of myocardial infarction and death. An elevation in the CD14++CD16+ cell population has been previously reported in patients with psoriatic disease, which has been confirmed in the coh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 57 publications
2
41
0
Order By: Relevance
“…Prior psoriasis studies on markers of local inflammation which are associated with an increased risk of CVD include myeloperoxidase, a pro-inflammatory heme protein released by myeloid cells (most likely released into circulation by MPO-producing skin-infiltrating myeloid cells), and resistin, an adipose-tissue derived hormone (most likely from adipose tissue subjacent to psoriasis plaques) [21][22][23][24][25]. In addition, we and others demonstrated that myeloid cells are altered in psoriasis patients, where the number of monocyte-derived suppressor cells (MDSCs) and intermediate (CD14 + CD16 + ) monocytes are increased in psoriasis patients, potentially as a result of similarly disordered myeloid cell release [24,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Prior psoriasis studies on markers of local inflammation which are associated with an increased risk of CVD include myeloperoxidase, a pro-inflammatory heme protein released by myeloid cells (most likely released into circulation by MPO-producing skin-infiltrating myeloid cells), and resistin, an adipose-tissue derived hormone (most likely from adipose tissue subjacent to psoriasis plaques) [21][22][23][24][25]. In addition, we and others demonstrated that myeloid cells are altered in psoriasis patients, where the number of monocyte-derived suppressor cells (MDSCs) and intermediate (CD14 + CD16 + ) monocytes are increased in psoriasis patients, potentially as a result of similarly disordered myeloid cell release [24,[26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…We previously reported increases in proinflammatory CD11b + Ly6C hi monocytes in KC-Tie2 mice (17,63) that precede the development of aortic root inflammation and shortened arterial thrombosis times, leading us to speculate that monocytes may participate in the thrombus formation. In mice with lengthened (protected) thrombosis clotting times (KC-Tie2xIL-6 -/-), we observed modest decreases in proinflammatory CD11b + Ly6C hi monocytes; however, these decreases occurred concomitantly with much larger reductions in circulating platelets and neutrophils, suggesting perhaps a more critical role for these cells in the promotion of thrombosis versus the monocytes.…”
Section: Mrp14mentioning
confidence: 99%
“…Eosinophils provide inflammatory signals that accelerate the pathogenesis of psoriasis [26]. High levels of monocytes indicate autoimmune disorders [27]. In auto-immune diseases, the immune system attacks and destroys RBC, platelets [28] and platelets may get trapped in the spleen [29].…”
Section: Discussionmentioning
confidence: 99%